Infants with dilated cardiomyopathy and hypocalcemia - Debmalya Sanyal (Indian Journal of Endocrinology and Metabolism, 2013)
Hypocalcemia is a rare reversible cause of dilated cardiomyopathy (DCM) and congestive heart failure; however, there are few reported cases, especially in infants. We describe 12 infants presenting with DCM and congestive cardiac failure who were found to have hypocalcemia. Vitamin D deficiency was the cause of hypocalcemia in all cases. The infants improved on supplementation with vitamin D and calcium.